Clinical outcomes of non-variceal upper gastrointestinal bleeding and its relation to aspirin and anticoagulants. - Radwan, Hend; Elsayed , Ehab; Alshabrawi, Hesham (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Non-variceal upper gastrointestinal bleeding (NVUGIB) is a life-threatening emergency that requires an urgent management. Antiplatelet (e.g., aspirin) and anticoagulant drugs are widely chronically used in various cardiac and coronary artery diseases. These drugs increase the risk of NVUGIB as they may cause ulceration of the upper gastrointestinal (GI) mucosa directly or may cause bleeding or rebleeding. The management of NVUGIB is complicated as the risk between GI bleeding episodes and cardiovascular attacks needs to be well managed. AIM: The aim of this study is to determine the impact of antiplatelets (aspirin) and anticoagulants use on the morbidity, mortality, and clinical outcomes in patients presented with non-variceal GI bleeding. PATIENTS AND METHODS: A total of 105 patients presented with melena and/or hematemesis and diagnosed by upper GI endoscopy were enrolled in a prospective cohort study. Patients were sub-grouped according to their use of antiplatelets, anticoagulants, or none (controls). Patients were excluded if they had portal hypertension or nonsteroidal anti-inflammatory drugs (NSAIDs) use and divided into five groups: Group I – patients who had not taken anticoagulants and antiplatelet; Group II – patients on heparin, warfarin, and LMWH only; Group III – patients on aspirin only; Group IV – patients on clopidogrel and ticlopidine with or without aspirin; and Group V – patients on combined anticoagulants and antiplatelet. All patients were subjected to clinical, laboratory (complete blood count, liver function tests, renal function tests, prothrombin time, and partial thromboplastin time), and endoscopic investigations. Clinical details were reported including admission, blood transfusion, rebleeding, and mortality. RESULTS: Full medical history revealed that 43 patients were diabetic, 45 patients were cardiac, and 67 patients were hypertensive. Regarding the history of analgesic drug intake, 38 patients used NSAIDs and 29 of them used non-selective NSAIDs and 8 patients used selective NSAIDs. There were non-significant differences among the studied groups with NVUGIB regarding sex, hematemesis only presentation, melena only presentation, liver function tests, and endoscopic findings. On the other hand, there were statistically significant differences between the studied groups with NVGIB regarding increasing age, NSAIDs use whatever selective or non-selective, decrease level of HB, WBCs, serum albumin, bleeding profile, kidney function tests, clinical presentation in the form of hematemesis and melena, need for blood transfusion, history of associated diseases, especially being cardiac patients, rebleeding after 6 and 12 months, and mortality. CONCLUSION: Aspirin intake may be associated with less favorable clinical outcomes in patients with NVUGIB, while combined anticoagulants and antiplatelets seem to be associated with the worse outcomes.